Pengalaman Ibu dengan Proses Menyusui - Sri Emilda; Wulandari (Jurnal Kesehatan dan Pembangunan, 2023)
Lactation management is an effort to support successful lactation starting during pregnancy, childbirth, and breastfeeding. The implementation of education on lactation management that has been taking place in health services is considered less successful because the education provided is less attractive to mothers. The purpose of this study was to find out in-depth information about mothers' experiences with lactation management. The research method used is descriptive quantitative. Informants in this study amounted to 3 informants consisting of 2 postpartum mothers who breastfeed their babies as main informants and 1 midwife as key informants. Sampling was done by purposive sampling method. Based on the results of interviews and observations of Informant 1; Mrs. H who always gave only breast milk to her baby while being carried and lying down, Mrs. H's baby seemed to be suckling strongly and fell asleep after feeding. Mrs. H never expresses breast milk, never does storage and never thaws breast milk. While Mrs. L always feeds her baby while being carried and if she is tired she will breastfeed lying down, Mrs. L's baby seems to be suckling strongly and falls asleep after feeding, sometimes Mrs. L does attachment by bringing the nipple closer to the baby's mouth . Mrs. L never expresses breast milk because her milk has come out so she has never stored and never thawed breast milk. Suggestions are expected that health workers, especially midwives, can further improve health promotion regarding lactation management to mothers as early as possible, starting from pregnancy, childbirth and post partum so as to improve the quality and coverage of exclusive breastfeeding for infants.